ESPON BANK SYARIAH KOTA BENGKULU TERHADAP KEWENANGAN PENGADILAN AGAMA PADA PENYELESAIAN SENGKETA PERBANKAN SYARIAH - Elman Johari (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2017)
Abstract: Sharia banking industry in Indonesia showed very rapid progress and Islamic principles which offered forbit riba,gharar, maisyir, and bathil. Nevertheless, the dispute in this industry will be inevitable, because the essence of dispute is a description to the harmonization of human interests. According the Article 49 point (i) of Law Number 3 of 2006 on the amendement of the Law Number 7 of 1989, Religious Court`s have the authority to settle the sharia economics disputes therein, includes Sharia Banking. This provision in contradict with the explaination of Article 55 clause (1) of Law Number 21 of 2008 about Sharia Banking which give the general court an authority to settle it disputes.